Artistic Arrangement as Semiotics of Criminal Messages in the Film “Marlina Si Pembunuh dalam Empat Babak” - Gea Refika Ayu Zellya; I Komang Arba Wirawan; I Dewa Made Darmawan (Institut Seni Indonesia Denpasar, 2022)
The purpose of this study is to determine semiotics in the artistic arrangement of criminal messages in the film “Marlina Si Pembunuh dalam Empat Babak” (Marlina the Murderer in Four Acts). It uses a qualitative descriptive method that describes in detail the problems shown in this study. The analysis technique used is Roland Barthes' semiotic analysis where this theory is divided into two i.e. signifier and signified. The concept used is criminal messages in the elements of artistic arrangement, then the theory is the semiotic theory from Roland Barthes. The messages in the film contains many criminal ones. The film has meanings of signifier and signified in each scene. The criminal messages include robbery, murder, rape, assault, and threats. The meaning of the criminal message in this film describes the mistakes in people's lives today. The film has applied good elements of artistic arrangement, which pays attention to the aesthetics of each shot, so that such a film is able to present messages that are in accordance with the reality in society.